Botulinum toxin and occupational therapy for Writer's cramp. (November 2019) - Park, Jung E.; Shamim, Ejaz A.; Panyakaew, Pattamon; Mathew, Pawan; Toro, Camilo; Sackett, Jonathan; Karp, Barbara; Lungu, Codrin; Alter, Katharine; Wu, Tianxia; Ahmad, Omar F.; Villegas, Monica; et al.
Abstract: Background: Writer's cramp (WC) is a form of focal hand dystonia, for which focal botulinum neurotoxin (BoNT) injections are the current best therapy. Past studies have shown that some types of rehabilitative therapy can be useful. We hypothesized that BoNT together with a specific type of occupational therapy would be better than BoNT alone for treating WC patients comparing the effects with a patient-rated subjective scale. Methods: Twelve WC patients were randomized to two groups. Six received only BoNT therapy and 6 received BoNT & occupational therapy. The occupational therapy involved specific exercises of finger movements in the direction opposite to the dystonic movements during writing. BoNT was injected by movement disorders neurologists in the affected muscles under electromyography-guidance. The primary outcome was the patient-rated subjective scale at 20 weeks. Secondary exploratory outcomes included the writer's cramp rating scale (WCRS), writer's cramp impairment scale (WCIS), the writer's cramp disability scale (WCDS), handgrip strength and kinetic parameters. Results: The patient-rated subjective scale scores at 20 weeks were not significantly different between the two groups. Significant objective improvement was noted in the BoNT & occupational therapy group, as noted by the decrease (28%) in WCIS scores. Conclusions: Improvement of the primary outcome measure, the patient-rated subjective scale, was not achieved. However, significant improvement was found in the BoNT & occupational therapy group in a secondary measure of impairment. Our hypothesis-driven study results are likely limited by small sample size, and further large-scale studies of occupational therapy methods to improve the efficacy of BoNT seems worthwhile. Highlights: Writer's cramp is a type of focal hand dystonia for which focal botulinum toxin injections are the current best therapy. We conducted a randomized, double-blinded study to study the additive effects of occupational therapy on focal hand dystonia. No significant improvement was found between the two groups; however, significant objective benefit in the group that also received occupational therapy was found. Our study results were drawn from a relatively small sample size and have limited significance; future large-scale study using occupational therapy methods to improve the efficacy of botulinum toxin injections seems worthwhile.